Detection of Degradation Effects in Field-Aged c-Si Solar Cells through IR Thermography and Digital Image Processing - E. Kaplani (International Journal of Photoenergy)
Due to the vast expansion of photovoltaic (PV) module production nowadays, a great interest is shown in factors affecting PV performance and efficiency under real conditions. Particular attention is being given to degradation effects of PV cells and modules, which during the last decade are seen to be responsible for significant power losses observed in PV systems. This paper presents and analyses degradation effects observed in severely EVA discoloured PV cells from field-aged modules operating already for 18–22 years. Temperature degradation effects are identified through IR thermography in bus bars, contact solder bonds, blisters, hot spots, and hot areas. I-V curve analysis results showed an agreement between the source of electrical performance degradation and the degradation effects in the defected cell identified by the IR thermography. Finally, an algorithm was developed to automatically detect EVA discoloration in PV cells through processing of the digital image alone in a way closely imitating human perception of color. This nondestructive and noncostly solution could be applied in the detection of EVA discoloration in existing PV installations and the automatic monitoring and remote inspection of PV systems.